PERFORMANCE OF THE SYAR'IYAH COURT IN HANDLING DIVORCE CASES IN CENTRAL ACEH REGENCY - Rinda Ramadani; Nur Hafni; Lisa Iryani; Ahmad Yani; Asrul Fahmi (RADJA PUBLIKA, 2025)
The Performance of the Sharia Court in Handling Divorce Cases in Central Aceh Regency with the increasing number of divorce cases every year, there were 538 cases in 2023, the cause of divorce cases was due to economic factors. This study aims to determine and analyze the performance of the Sharia Court in handling divorce cases in Central Aceh Regency and identify the obstacles faced with the focus of this research is to see performance with aspects of service quality and responsibility. This study uses a qualitative research method with a descriptive approach. This study uses two data sources: primary data in the form of interviews, field observations, and documentation, and secondary data, namely SOPs, Regulations and documents, as data collection techniques. The results of this study indicate that the performance of the Sharia Court in handling divorce cases is not optimal, especially in the mediation process which still takes a long time and the low success rate of mediation. The main factors causing divorce cases are economic problems and dependence on online gambling which affects the husband's financial ability. The obstacles faced are the absence of one of the parties, excessive emotions from both parties in the case and the limited number of mediators.